Iron therapy in pregnant women with iron deficiency anemia: a meta-analysis - Natarajan, Anusha; Baskaran, Priyadarsini (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Pregnancy significantly increases the need for iron. The prevalence of anemia in pregnant women is high, affecting 41.8% of all pregnant women worldwide. In patients with low tolerance to oral iron, it is recommended to start them on parenteral iron therapy but with variable degree of efficacy. Hence this meta-analysis was done with the following aim. This study aimed to assess the efficacy of various iron preparations in pregnant women with iron deficiency anemia (IDA). Methods: Randomised controlled trials (RCTs) (available as full free text) which included iron therapy in pregnant women with iron deficiency anemia were retrieved from electronic databases viz. PubMed, Google scholar and IndMed, with specific search terms. Qualities of RCTs were assessed using JADAD score and four RCTs with high score were included for analysis using RevMan 5.3 software. Outcome measures were change in hemoglobin levels and serum ferritin concentration after one month of therapy. Results: In the four RCTs included, a total of 267 patients were treated with oral iron and 267 patients were treated with parenteral iron therapy. Change in the hemoglobin levels between the 2 groups had a standard mean difference of 0.73, 95% CI (-0.05-1.52), with the p-value of 0.07. To assess the change in the serum ferritin concentration a total of 188 patients in oral iron and 197 patients in parenteral iron therapy were included. There was a standard mean difference of 0.88, 95% CI (0.60-1.66), with a p value of<0.00001. Conclusions: In the present meta-analysis we found that oral and parenteral iron therapy showed similar efficacy in improving the hemoglobin level in pregnant women.